2011
DOI: 10.1680/ensu.2011.164.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Mapping sustainability assessment with the project life cycle

Abstract: 2 3Traditionally viewed as a technically based exercise focused on assessing the sustainability performance of buildings, sustainability assessment is increasingly called upon to play a proactive role that supports the management of sustainability across the project life cycle. Calls are emerging for assessment to evolve as a tool that contributes to the predominantly subjective nature of decisions taken across the project life cycle and to achieve better integration between assessment and project activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…An attempt has been carried out to integrate sustainability and project management by few researchers namely Silvius et al (2013, 158 2017), Gareis et al(2013), Carvalho (2016a, 2016b), Sánchez (2015), Silvius (2013), Bernhardi et al (2000), Bodea et al (2010), Fernández andRodríguez-López (2010), Hartig et al(1996), Jones (2006), Raven et al (2009), Turlea et al (2010) and Vifell and Soneryd (2012). From the literature, a lot of research scope have been found for the development of the models, tools, methods, and techniques to integrate and gauge the sustainability and the project management (Singh et al, 2012;Thomson et al, 2011;John et al 2016). The developed methods and models further can be extensively used by the companies for assuring the sustainability at the project level or at the organization level (Cole, 2005;Deakin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An attempt has been carried out to integrate sustainability and project management by few researchers namely Silvius et al (2013, 158 2017), Gareis et al(2013), Carvalho (2016a, 2016b), Sánchez (2015), Silvius (2013), Bernhardi et al (2000), Bodea et al (2010), Fernández andRodríguez-López (2010), Hartig et al(1996), Jones (2006), Raven et al (2009), Turlea et al (2010) and Vifell and Soneryd (2012). From the literature, a lot of research scope have been found for the development of the models, tools, methods, and techniques to integrate and gauge the sustainability and the project management (Singh et al, 2012;Thomson et al, 2011;John et al 2016). The developed methods and models further can be extensively used by the companies for assuring the sustainability at the project level or at the organization level (Cole, 2005;Deakin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pope et al (2004) and Wilkins (2003) observed that all stakeholders of a project should decide their priorities after analyzing the effects of the project life-cycle under consideration on the throughout sustainability of the projects. Further, the evaluation of the sustainability should have some critical parameters to gauge the sustainability and can play a decisive and transparent role for all the stakeholders while taking significant decisions in the management of the projects (Mathur et al, 2008;El-Haram et al, 2007;Thomson et al, 2011). Singh et al (2012), ElHaram et al (2007) and Thomson et al (2011) found that conceptual and technical issues for the sustainable project management are yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And project management could make a valuable contribution in this context [3,4]. Today it is increasingly well understood that methods, tools and techniques need to be developed to integrate sustainability criteria into the management of projects [5,6]; moreover, there is a growing need of knowledge and concepts how to incorporate sustainability into the project management process [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The final paper in the issue (Thomson et al, 2011) presents the authors' experience of sustainability assessment (SA) at a single project scale. The paper highlights the technology-social interplay, stating that whilst SA used to be regarded as a technology-driven add-on to project appraisal, it is far more powerful in achieving sustainable outcomes when used as a project-scale governance mechanism.…”
mentioning
confidence: 99%